Elucidation of blended cement using industrial waste - Doh, Shu Ing
Urban population of Malaysia is stated as 72.8% of its total population, and growing every year. Due to this growing number of population, the sewage sludge waste produce every year has also gradually increased. Malaysia itself produces 3.2 million m3 of sewage sludge annually. Normally all of this waste is disposed by landfill. This was a serious threat to the environment due to the toxic content of sewage sludge if it is dump away without proper measures. The increasing rate of production of sewage sludge waste has called for an alternatives way to develop good quality of construction material from waste resources. Furthermore, usual production of cement and sewage sludge ash consumes a lot of energy by using incineration process with a very high temperature. Thus microwave heating method was an alternatives use in this research to reduce the consumption of energy and time used to heat the sewage sludge ash. This research was conducted to investigate the optimum performances of different percentage (0%, 5%, 10%, 15% and 20%) by weight of cement of the Microwaved Sewage Sludge Ash (MSSA) concrete with different curing regime, which was air and water curing, its mechanical properties and also durability properties. The characteristic of MSSA was tested by X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The mechanical properties of MSSA concrete was examined by Compressive Strength test, Flexural Strength test and Modulus of Elasticity test after 180 days of curing. While, the Durability properties of the MSSA concrete were identified by using Acid attack test, Sulphate resistance and water absorption test. Based on the results, water curing with 5% of MSSA had the best in results compared to other specimens. The mechanical properties of 5% MSSA content in concrete shows the most optimum samples due to the densification of pozzolanic reaction and filler effect of MSSA. The lowest mechanical performance was 20% MSSA. The curing effect with better result was water curing, as it got highest value of strength in compressive test, flexural test and modulus of elasticity test. Water curing with 5% MSSA also shows best in durability resistance towards sulphate and acid attack. As for water absorption test, all of the specimen shows better result as it is below than 10% rate of absorption. As conclusion, based on the results, it is shown the positive impact on using the MSSA as additional material to the cement mixture to improve the quality of the concrete. Thus, this will reduce the disposal of sewage sludge ash waste on dumping site and improves the quality performances of the concrete.